In vivo risk evaluation of carbon-coated iron carbide nanoparticles based on short- and long-term exposure scenarios. (April 2016) - Herrmann, Inge K; Beck-Schimmer, Beatrice; Schumacher, Christoph M; Gschwind, Sabrina; Kaech, Andres; Ziegler, Urs; Clavien, Pierre-Alain; Günther, Detlef; Stark, Wendelin J; Graf, Rolf; Schlegel, Andrea A
Background: While carbon-encapsulated iron carbide nanoparticles exhibit strong magnetic properties appealing for biomedical applications, potential side effects of such materials remain comparatively poorly understood. Here, we assess the effects of iron-based nanoparticles in an in vivo long-term study in mice with observation windows between 1 week and 1 year.Materials & methods: Functionalized (PEG or IgG) carbon-encapsulated platinum-spiked iron carbide nanoparticles were injected intravenously in mice (single or repeated dose administration).Results: One week after administration, magnetic nanoparticles were predominantly localized in organs of the reticuloendothelial system, particularly the lung and liver. After 1 year, particles were still present in these organs, however, without any evident tissue alterations, such as inflammation, fibrosis, necrosis or carcinogenesis. Importantly, reticuloendothelial system organs presented with normal function.Conclusion: This long-term exposure study shows high in vivo compatibility of intravenously applied carbon-encapsulated iron nanoparticles suggesting continuing investigations on such materials for biomedical applications.